2017
DOI: 10.1149/2.0491713jes
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Insertion in Nanostructured Si1-xTixAlloys

Abstract: Nanostructured Si 1-x Ti x alloys (0 ≤ x ≤ 0.3) prepared by ball milling were studied as negative electrode materials in Li cells. The alloys comprised a nanocrystalline and amorphous Si phase and a nanocrystalline C49 TiSi 2 phase. When x ≥ 0.15 the nanocrystalline Si phase was completely eliminated and such alloys consisted only of amorphous Si and the C49 TiSi 2 phase. The alloys with x ≥ 0.15 also completely suppressed the formation of Li 15 Si 4 during cycling, resulting in good capacity retention, and, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 16 publications
(27 reference statements)
0
40
0
Order By: Relevance
“…Since c -Li 3.75 Si only forms below 50 mV vs Li, ,,, sufficiently high stress can prevent this phase from forming. In one approach, Obrovac and co-workers prepared a series of silicon alloys with transition metals including Ti, Ni, and Cu, both as powders and thin films. c -Li 3.75 Si was suppressed in both the powder and thin film electrodes which was ascribed to increased stress induced by crystalline intermetallic inclusions in the powders and the dissolved transition metal atoms in the thin films. …”
Section: Introductionmentioning
confidence: 99%
“…Since c -Li 3.75 Si only forms below 50 mV vs Li, ,,, sufficiently high stress can prevent this phase from forming. In one approach, Obrovac and co-workers prepared a series of silicon alloys with transition metals including Ti, Ni, and Cu, both as powders and thin films. c -Li 3.75 Si was suppressed in both the powder and thin film electrodes which was ascribed to increased stress induced by crystalline intermetallic inclusions in the powders and the dissolved transition metal atoms in the thin films. …”
Section: Introductionmentioning
confidence: 99%
“…The Cu/Ni/Si85Ti15 electrode shows improved capacity retention of 82% after 200 cycles; Wang et al reported similar results for Ti-Si alloys and attributed the observation to the suppression of the c-Li3.75Si phase. 25 Compared to the Cu/Ni/Si85Ti15 electrode, addition of carbon (10 nm) or TiO2 (5 or 10 nm) capping layers exhibits further improvement in capacity retention as well as CE. The improvement in CE might result from less (or different) SEI formation, although this remains to be determined (vide infra).…”
Section: Electrode Preparation and Battery Assemblymentioning
confidence: 98%
“…This is also true for alloying with the hard non-active transition metal inclusions, titanium in our case, which generate internal stresses in the silicon film. [25][26][27][28] However, with each delithiation cycle, there is a non-zero amount of fracture that occurs. Pores and fractures between 'islands' result in additional free volume for expansion in the electrode material, as is visible in the SEM micrographs in Figure 2 and is often observed during lithiation-delithiation cycling of silicon thin films.…”
Section: M45mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the relatively small additional capacity and expansion associated with its formation, c -Li 15 Si 4 has been linked to an increased loss of capacity in both silicon thin films , and nanoparticles. , The observed links between delamination, capacity loss, and the c -Li 15 Si 4 phase are convoluted in thin films. The presence of c -Li 15 Si 4 is near-ubiquitous when delamination is observed in thin films, but this crystalline phase is also generally accepted to play an intrinsic role in capacity degradation beyond catastrophic delamination .…”
Section: Introductionmentioning
confidence: 99%